Portable Microfluidic Integrated Plasmonic Platform for Pathogen Detection - Tokel, Onur; Yildiz, Umit Hakan; Inci, Fatih; Durmus, Naside Gozde; Ekiz, Okan Oner; Turker, Burak; Cetin, Can; Rao, Shruthi; Sridhar, Kaushik; Natarajan, Nalini; Shafiee, Hadi; Dana, Aykutlu; et al. (Scientific reports, 2015)
Timely detection of infectious agents is critical in early diagnosis and treatment of infectious diseases. Conventional pathogen detection methods, such as enzyme linked immunosorbent assay (ELISA), culturing or polymerase chain reaction (PCR) require long assay times and complex and expensive instruments, which are not adaptable to point-of-care (POC) needs at resource-constrained as well as primary care settings. Therefore, there is an unmet need to develop simple, rapid and accurate methods for detection of pathogens at the POC. Here, we present a portable, multiplex, inexpensive microfluidic-integrated surface plasmon resonance (SPR) platform that detects and quantifies bacteria, i.e. , Escherichia coli ( E. coli ) and Staphylococcus aureus ( S. aureus ) rapidly. The platform presented reliable capture and detection of E. coli at concentrations ranging from ~10 5 to 3.2 × 10 7 CFUs/mL in phosphate buffered saline (PBS) and peritoneal dialysis (PD) fluid. The multiplexing and specificity capability of the platform was also tested with S. aureus samples. The presented platform technology could potentially be applicable to capture and detect other pathogens at the POC and primary care settings.